Options, futures, and other derivatives - John C. Hull (Pearson Education, 2024)
Through its coverage of important topics such as the securitization and the credit crisis, the overnight indexed swap, the Black-Scholes-Merton formulas, and the way commodity prices are modeled and commodity derivatives valued, it helps students and practitioners alike keep up with the fast pace of change in today's derivatives markets.